Evaluating the Efficiency of Batam’s Regional Investment Policies: Challenges and Solutions for Sustainable Economic Growth - Nanda Dwi Angraeni; Lubna Salsabila; Timbul Dompak; Iranda Firiansyah (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to evaluate the efficiency of Batam’s regional investment policies, focusing on their effectiveness in fostering sustainable economic growth. Batam, one of Indonesia's fastest-growing cities, has experienced significant industrial development, making investment policies a crucial factor in ensuring continued economic progress. The research examines key aspects of these policies, including efforts to reduce bureaucracy in investment processes, create incentives that align with regional development goals, and enhance the monitoring of investment activities. By analyzing the current policies through a comprehensive evaluation framework, this study identifies challenges such as institutional dualism, legal uncertainties, and slow investment growth, which hinder the city's economic development. Additionally, it explores solutions for optimizing these policies to improve their efficiency, thereby contributing to sustainable growth and greater competitiveness for Batam. The findings of this study provide critical insights for policymakers seeking to enhance Batam's investment climate and overall economic performance.